Pendidikan Kristen dan Moralitas di Dunia Digital:: Integrasi Teologi dalam Pembentukan Etika di Era Teknologi bagi Generasi Alpha - Arifianto, Yonatan Alex; Sumual, Elisa Nimbo; Rahayu, Yohana Fajar (Sekolah Tinggi Agama Kristen Samarinda, 2025)
Abstract: The development of digital technology has brought significant changes in social and cultural life and spirituality, especially for the Alpha generation who grew up in the digital era and the globalisation of the internet of thoughts. The influence of social media, digital content, and virtual interaction in the gadget world has affected their mindset and moral behaviour. Therefore, Christian education, which is supposed to shape character and morality based on the teachings of Christ, is faced with great challenges in teaching ethical values in the midst of the rapid development of cyberspace which often contradicts moral principles and Christian values. This research aims to examine the role of Christian education in shaping the morality of the Alpha generation in the digital world, with a focus on the integration of theology in relevant theological ethical teaching. Using a descriptive qualitative method with a literature study approach. The conclusion of this study shows that the integration of theological teachings in Christian education can strengthen the foundation of Alpha generation morality, by emphasising biblical values in their digital life. Such as the paradigm of the concept of Christian morality and ethics in the digital context and the existence of morality issues in the digital world for the alpha generation that must be resolved. So that Christianity has an educational role in shaping morality in the digital world, which is based on theology-based Christian education for ethical formation in the digital era. Abstrak: Perkembangan teknologi digital telah membawa perubahan signifikan dalam kehidupan sosial dan budaya serta spiritualitas, khususnya bagi generasi Alpha yang tumbuh dalam era digital dan globalisasi internet of thinks. Pengaruh media sosial, konten digital, dan interaksi virtual dalam gawai telah memengaruhi pola pikir dan perilaku moral mereka. Maka itu pendidikan Kristen, yang seharusnya membentuk karakter dan moralitas berdasarkan ajaran Kristus, dihadapkan pada tantangan besar dalam mengajarkan nilai-nilai etika di tengah pesatnya perkembangan dunia maya yang seringkali bertentangan dengan prinsip moral dan nilai kekristenan. Penelitian ini bertujuan untuk mengkaji peran pendidikan Kristen dalam membentuk moralitas generasi Alpha di dunia digital, dengan fokus pada integrasi teologi dalam pengajaran etis teologis yang relevan. Menggunkan metode kualitatif deskritif dengan pendekatan studi pustaka. Kesimpulan penelitian ini menunjukkan bahwa integrasi ajaran teologi dalam pendidikan Kristen dapat memperkuat dasar moralitas generasi Alpha, dengan menekankan nilai-nilai alkitabiah dalam kehidupan digital mereka. Moralitas dan etika kristen dalam konteks digital dan adanya persoalan moralitas dalam dunia digital bagi generasi alpha yang harus diselesaikan. Sehingga kekristenan memiliki peran pendidikan dalam membentuk moralitas di dunia digital, yang mana ini didasarkan pada pendidikan Kristen berbasis teologi untuk pembentukan etika di era digital.